Commissioning Of The Ground Control Station For HAB System - Afzan, Tengku Muhammad Faris Tengku (Universiti Sains Malaysia, 2017)
Glider is a vehicle that operates with no power supply and unmanned operating system. There are many types of glider that consist of the certain purpose of activities. Long range glider is referring to a glider that can be glide with a range and time. The impact of having a glider in the industry is too able an aircraft glide in emergency condition. The glider are going through design phase which consists of preliminary design and final design before undergo fabrication process. The fabrication process of the glider is using the balsa wood as the main materials for the wing and tail part besides the composite materials is used for the fuselage and the attachment between the wing and the fuselage. The purpose of the attachment is to attach the different types of the wing on the fuselage. The logic of the attachment is the glider have been construct with three different wings to determine the performance of the glider in term of the range while the other part are fixed. The test model are held at the different locations such as field test and stage test which the results of the test come out with the stage test are the highest with the range of 57.4 metre in 15.76 second of the gliding duration. The overall results state that the dihedral wing is the best performance wing followed by tapered and straight wing. The reason is the dihedral wing returns the wing to level when there is disturbance. The result obtain from the technique applied on the glider are record, compared and analysed in the current study.